"An Act of Complete Care": Provider Perspectives on Linking Maternal Contraceptive Care With Well-Baby Visits in Community Health Centers - Amanda Knepper; Alejandra Zocchi; Sadia Haider; Rachel Caskey (SAGE Publishing, 2024)
Background: Short inter-pregnancy interval (IPI) is associated with adverse health outcomes for women and infants, and low-income women experience disproportionate rates of short IPI. An essential solution is providing postpartum (PP) women with timely contraceptive care. However, patient-centered approaches for facilitating care access are needed. Objective: To explore Community Health Center (CHC) staff and provider perspectives on the implementation of a clinical trial offering co-scheduled well-infant/maternal contraceptive care for women with infants 0 to 6 months at the Well-Baby Visit (WBV). Method: Eighteen participants (providers, staff, and administrators) representing 7 diverse CHC sites in 2 U.S. states completed semi-structured telephone interviews. Audio-recordings were transcribed and analyzed using hybrid thematic analysis. Results: Offering co-scheduled visits was perceived as beneficial for facilitating timely PP contraception, convenient care access, and encouraging family planning considerations during the PP period. However, provider and staff discomfort with initiating family planning and contraceptive care conversations at the WBV emerged as a salient barrier. Conclusion: Paired approaches to well-infant/maternal contraceptive care may promote increased access to timely contraception for PP women, possibly reducing unintended short IPI. Comprehensive training, ongoing support, and patient-centered implementation strategies tailored to context and developed with care team input are needed to ensure competency and comfortability with facilitating contraceptive care conversations at the WBV.